Design of CMOS Current-mode Multiplier-Divider circuit for type-2 FLC Applications - Santos, Rodrigo Bispo dos [UNESP]; Rocha Rizol, Paloma M. S. [UNESP]; Mesquita, Leonardo [UNESP]; Arnaud, A.; Silveira, F.; Garcia, L. (Ieee, 2015)
The design of a low voltage current-mode CMOS multiplier/divider circuit is presented in this paper. This circuit is used to implement the type-reducer block of Type-2 Fuzzy Logic Controller chip. The simulation results of multiplier/divider circuit have been done in CMOS 0.35 mu m technology through Pspice software using a single supply voltage of 1.8V.
Keywords: component; Multiplier/divider; Type-2 fuzzy logic; Interval type-2 fuzzy logic controller